Effect and mechanism of NaHS on tobacco bacterial wilt caused by Ralstonia solanacearum - Dingxin Wen; Qingqing Guo; Wan Zhao; Yong Yang; Chunlei Yang; Jun Yu; Yun Hu (Scientific Reports, 2023)
Abstract Since its discovery as a third unique gaseous signal molecule, hydrogen sulfide (H2S) has been extensively employed to resist stress and control pathogens. Nevertheless, whether H2S can prevent tobacco bacterial wilt is unknown yet. We evaluated the impacts of the H2S donor sodium hydrosulfide (NaHS) on the antibacterial activity, morphology, biofilm, and transcriptome of R. solanacearum to understand the effect and mechanism of NaHS on tobacco bacterial wilt. In vitro, NaHS significantly inhibited the growth of Ralstonia solanacearum and obviously altered its cell morphology. Additionally, NaHS significantly inhibited the biofilm formation and swarming motility of R. solanacearum, and reduced the population of R. solanacearum invading tobacco roots. In field experiments, the application of NaHS dramatically decreased the disease incidence and index of tobacco bacterial wilt, with a control efficiency of up to 89.49%. The application of NaHS also influenced the diversity and structure of the soil microbial community. Furthermore, NaHS markedly increased the relative abundances of beneficial microorganisms, which helps prevent tobacco bacterial wilt. These findings highlight NaHS's potential and efficacy as a powerful antibacterial agent for preventing tobacco bacterial wilt caused by R. solanacearum.